Changes in prescription drug abuse during the COVID-19 pandemic evidenced in the Catalan pharmacies - Perelló, Maria; Rio-Aige, Karla; Rius, Pilar; Bagaría, Guillermo; Jambrina, Anna M.; Gironès, Montse; Pérez-Cano, Francisco José; Rabanal, Manel (Frontiers in Public Health, 2023)
Introduction The impact of a pandemic on the mental health of the population is to be expected due to risk factors such as social isolation. Prescription drug abuse and misuse could be an indicator of the impact of the COVID-19 pandemic on mental health. Community pharmacists play an important role in addressing prescription drug abuse by detecting signs and behaviors that give a clearer indication that a drug abuse problem exists. Methods A prospective observational study to observe prescription drug abuse was conducted from March 2020 to December 2021 to compare with data obtained in the previous two years, through the Medicine Abuse Observatory, the epidemiological surveillance system set up in Catalonia. Information was obtained through a validated questionnaire attached on a web-based system and data collection software. A total of 75 community pharmacies were enrolled in the program. Results The number of notifications during the pandemic period (11.8/100.000 inhabitants) does not indicate a significant change compared with those frome pre-pandemic period, when it was 12.5/100.000 inhabitants. However, the number of notifications during the first wave when lockdown was in place stood at 6.1/100,000 inhabitants, significantly lower than in both the pre-pandemic and the whole of the pandemic periods. Regarding the patient’s profile, it was observed that the proportion of younger patients (<25 and 25-35) rose in contrast to older ones (45-65 and >65). The use of benzodiazepines and fentanyl increased. Conclusions This study has made it possible to observe the impact of the pandemic caused by COVID-19 on the behavior of patients in terms of use of prescription drugs through analysis of the trends of abuse or misuse and by comparing them with the pre-pandemic period. Overall, the increased detection of benzodiazepines has pointed out stress and anxiety generated by the pandemic.